Fasting-induced torpor in mice: effects on sleep and behaviour - Wilcox, SL (2023)
Torpor is a state of profoundly altered physiology, characterised by metabolic suppression and concurrent hypothermia. Relatively little is understood about torpor, and few researchers are aware that laboratory mice enter this state in response to limited food availability. The aim of this thesis was to further the understanding of torpor by investigating its interaction with sleep and the circadian system, and the effect of torpor on behaviour. Further, a secondary aim was to investigate the potential for torpor to be a cofounding factor in studies that use fasting techniques. First, this thesis characterised torpor induction and propensity in response to a common food restriction paradigm. Meal timing was found to significantly alter torpor characteristics, providing further evidence for the circadian control of torpor. As this food restriction protocol is commonly used within behavioural neuroscience, the effect of torpor induction on performance in behavioural tasks was investigated. This revealed that time of testing relative to torpor significantly impacted locomotor activity. Next, the relationship between sleep and torpor was investigated using chronic electroencephalography, and sleep deprivation and auditory stimulation techniques. Brain activity during torpor closely resembled sleep, although sleep-wake architecture was profoundly altered in the presence of torpor. An increase in sleep intensity following torpor was observed, suggesting that torpor may be a sleep depriving state. For the first time, auditory evoked responses were recorded in torpid mice, revealing a marked similarity with responses recorded during sleep, although response dynamics were found to differ between sleep and torpor. Finally, this thesis presents pilot data which suggests that water restriction does not result in torpor induction in mice, indicating that water restriction may be a suitable alternative to food restriction to avoid torpor. Overall, this thesis provides novel insights into the characteristics, neurophysiology, and regulation of fasting-induced torpor in mice. Moreover, the data presented here highlight the potential for torpor to be a potential confound in research using fasting techniques if not adequately controlled for.